Violence and sexual harassment in Nigerian novels: the nego-feminist option - Alkali, Muhammad; Talif, Rosli; Mohd Jan, Jariah (International Institute for Science, Technology & Education, 2013)
Taking advantage of women in most modern legal contexts is illegal. The unwelcome sexual advances have often been accompanied with violence of differing degrees. Such advantages from sexual abuse or sexual assault into forced marriages and to mild transgressions that include simple teasing, offhand comments, or minor isolated incidents in the life cycle of a female such as demonstrated in Buchi Emecheta’s The Bride Price (1976) forcefully calls attention to how they should be remedied. In the village of Ibuza, harassment is so frequent and severe that it creates a hostile and offensive environment for budding girls of marriage age – and a question shoots: what is the way out for novelists in deconstructing the life of such young girls as Aku-nna, the lead female character? While Emecheta takes the option of a strong backlash on the male class, new female writers like Ify Osammor in her The Triumph of Water Lily (1996) have made feminism to evolve by certainly bringing to disrepute the oddity of the male but in an amiable way that would appear to yield better results. This option of Nego-feminism charges both sexes to be willing-partners in progress. The option speaks in the monologic voice of unquestioned authority, determined by experience, knowledge and practice. Its dialogic (competing) voices speak in new official language and new official thought. In short, where the arrant feminism is a closed gender genre reflective of what has already occurred, Nego-feminism is open — to the present and the future. As such, the novel is almost by definition a progressive genre, which Osammor uses the different expectations that society holds for gender roles to twist the tragic situation of The Triumph of Water Lily into a tighter knot than radical events would otherwise permit.